GENRE ANALYSIS OF THE ENGLISH FINAL PROJECT ABSTRACTS WRITTEN BY THE STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF IKIP PGRI SEMARANG - Wiyaka, Wiyaka; Wahyuni, Sri; Setyorini, Ajeng (Kajian Linguistik dan Sastra, 2010)
This study is specifically focused on the student final project abstract based on genreÂ analysis which covers the study of the generic structure and the linguistic features. TheÂ statements of the study are: (1). How do the students of English Education DepartmentÂ of IKIP PGRI Semarang realize the generic structure in their final project abstracts (2).Â How do they realize the linguistic features in their final project abstracts, and (3). WhatÂ is the contribution of the result of the study to the English Education Program of IKIPÂ PGRI Semarang. The main purpose of this study is to find out the generic structure andÂ linguistic features of the final project abstracts and analyze the contribution of thisÂ study to the English Department. This study applies the descriptive qualitative method.Â The object of this study is the final project abstracts written by English EducationÂ Department students of âIKIP PGRI Semarangâ. The total of 10 final projects formedÂ the data of this study. The data of the study were analyzed using the genre analysisÂ approach. The first step of data analysis was identifying the Moves which was done byÂ using Linguistic evidence and understanding the texts. The finding shows that onlyÂ some of the final project abstracts made by the students of IKIP PGRI applied the fiveÂ Moves. It is found that two Moves are applied in all abstracts, they are Purpose andÂ Method Moves (100%). Situating the research is used in five abstracts (50%). Meanwhile the third move that is the Result Move used in eight abstracts (80%). The Conclusion Move found in five abstracts (50%). The result of the analysis showed that twoÂ personal pronouns were found in the final project abstracts. Personal pronouns such asÂ âthe writerâ and âthe researcherâ were found in all of the abstracts. Personal pronounÂ âsheâ was found in one abstract. Finally, there are only five expressions of hedges thatÂ are used in the final project abstracts, they are modal auxiliary verbs, adjectival, adverbial, nominal and Approximators of degree. The suggestions toward this study areÂ (1) The English lecturers should introduce how to create a meaningful text, particularlyÂ the abstract as the representation of the research report in good structure for the students based on the theory of genre. (2) The lecturers should improve the teaching andÂ learning process relating to the improvement of academic writing, in this case lecturersÂ who in charge of teaching academic writing. (3) The final project supervisors shouldÂ put a high concern of genre to be applied in writing the abstract of the final projectÂ during the supervision. (4) The English Education department should provide a preciseÂ guideline for final project writing.Key words: genre, final project, abstract.